2012
DOI: 10.1080/09593330.2012.655316
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of polyaromatic hydrocarbons and volatile organic compounds in two major traffic tunnels in Seoul, Korea

Abstract: To describe the fundamental aspects of air quality in tunnel environments, field campaigns were conducted to measure polycyclic aromatic hydrocarbons (PAHs), volatile organic compounds (VOCs), and some criteria pollutants from two tunnel sites of Nam San (NS) and Hong Ji (HJ) gates in Seoul, Korea. The total PAH values (ngm(-3)) for the NS tunnel (137.8 +/- 10.9) were notably higher than the HJ counterpart (91.3 +/- 7.82), while the total VOC exhibited a reversed pattern with a notable enhancement in the HJ tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Figure 4 shows the ratio of BaP and BgPe in the atmosphere at the three different functional sites in Hanoi in this study and different emission sources in the previous studies. According to ours and other previous studies on the different emission sources of atmospheric PAHs and NPAHs, the [BaP]/[BgPe] ratios are between 0.08 and 0.49 in motorcycle emissions [42,[69][70][71][72][73], 0.6 and 1.64 in biomass burning [74][75][76][77][78][79] and 0.53 and 0.90 in automobile emissions [6,[80][81][82][83][84][85]. In this study, the ranges of [BaP]/[BgPe] in summer were 0.34-0.47 (GL), 0.23-0.34 (XT) and 0.26-0.42 (DA), which are close to the emission characteristics of motorcycles.…”
Section: Prospective Emission Sources Of Pahs and Npahssupporting
confidence: 61%
“…Figure 4 shows the ratio of BaP and BgPe in the atmosphere at the three different functional sites in Hanoi in this study and different emission sources in the previous studies. According to ours and other previous studies on the different emission sources of atmospheric PAHs and NPAHs, the [BaP]/[BgPe] ratios are between 0.08 and 0.49 in motorcycle emissions [42,[69][70][71][72][73], 0.6 and 1.64 in biomass burning [74][75][76][77][78][79] and 0.53 and 0.90 in automobile emissions [6,[80][81][82][83][84][85]. In this study, the ranges of [BaP]/[BgPe] in summer were 0.34-0.47 (GL), 0.23-0.34 (XT) and 0.26-0.42 (DA), which are close to the emission characteristics of motorcycles.…”
Section: Prospective Emission Sources Of Pahs and Npahssupporting
confidence: 61%
“…There were obvious differences in the PAH congeners/homologue distributions between the used and unused PPEs, in which the low-molecular-weight (LMW) PAHs (i.e., 2–3 rings) were predominant in the unused PPE (i.e., 90.9–95.3%), while the high-molecular-weight (HMW) PAHs (i.e., 4–6 rings) were predominant in the used PPE (i.e., 52.1–74.5%), thereby showing a reflection of their contamination source profiles. LMW-PAHs with ≤3 rings are generally known to be volatile, hence tending to partition in the gas phase, , leading to their widespread contamination, which could explain their relative abundance in both used and unused PPEs. However, in contrast to the unused PPE, there was a shift toward the dominance of HMW-PAHs in the used PPE, suggesting an occupational contamination effect from exposure at fire sites because HMW-PAHs (≥4 rings) are generally considered to originate primarily from pyrogenic sources. , A further exploration of the distribution characteristics of PAHs using PCA showed that the used PPEs were clearly distinguished from the unused PPEs (Figure d), thereby supporting our discussions above.…”
Section: Resultsmentioning
confidence: 99%
“…PAH compositions in samples have been demonstrated to depend on their emission sources; hence, molecular diagnostic ratios (MDRs) are frequently used to trace the possible origins of PAHs in environmental samples by calculating the ratios of PAH isomers having similar physicochemical properties, such as molecular weight. However, it is recommended that the application of these ratios be approached with great caution as they are only indicative owing to factors that can alter the distribution profile of PAHs in samples over time, such as photodegradation and long-range atmospheric transport/deposition of PAHs. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tunnel with a semi-enclosed space can be selected to investigate the characteristic of pollutants discharged from a wide ranges of vehicle type (or fleet composition) operated at different conditions because of the least influences of meteorological parameters and atmospheric reactions occurring inside the tunnel (Kim et al, 2012). This study conducted the tunnel sampling with the primary aims to (1) characterize the distribution of 25 PAHs in particulate phase (PM2.…”
Section: Accepted Manuscriptmentioning
confidence: 99%